Real and Accrual-Based Earnings Management in the Pre- and Post-Audit-Reform Period: Evidence from UK - Tanveer, Amir (2018)
The study is based on a sample of 5,514 publicly listed firms in the UK. I investigate the changes in earnings management for the post period (2017) versus the pre (2016). The results suggest mandatory audit-reform adoption does not materially impact the level of accrual-based and real earnings management. The results of this research do not conclude that the new standards and regulations are of no importance but suggests that there may be other factors that might help to explain the influence on earnings management practices better. Even though a significant impact was not found during the post period yet the switch between the two earning management strategies was evident. The findings regarding the association between the domination of the big 4 and non-audit service fees with earnings management also provide additional insight into the extensive debated literature (DeAngelo, 1981; Francis and Yu, 2009; Harris and Whisenant, 2012; Lennox et al., 2014). A significant relationship was not found with the audit quality variables whereas similar research that focuses on audit quality using comparable variables (big 4 and non-audit fees) have found meaningful associations with earnings management proxies (Chi et al., 2011; Zang, 2012). These substantial studies have focused mainly on a US setting that could suggest that the earnings game could be played differently in the UK.